Effect of oxidative stress on aorta and tibia osteoprotegerin gene expression in ovariectomized rats - (:unkn) unknown (EDIZIONI MINERVA MEDICA, 2011)
Aim. Atherosclerosis and osteoporosis share some common pathophysiological pathways. Increase in oxidative stress and activation of cytokines that increase osteoclastogenesis were reported in postmenopausal period. The aim of this study was to determine the link between these two states. Methods. A total of 32 female adult Wistar albino rats were included in the study. Rats in control group were sham operated, vehicle group were ovariectomized and given 17.5%hydroxypropyl-beta-cyclodextrin. Rats in group III and IV were ovariectomized and given 17 beta-estradiol or raloxifene for 12 weeks, respectively. Aorta and tibia bone samples were collected. Tissue oxidative stress was determined via measurement of malondialdehyde levels and osteoprotegerin gene expression with RT-PCR. Results. Ovariectomy increased MDA levels both in bone and aorta compared to sham operated rats. Use of 17 beta-estradiol or raloxifene did not create a significant difference compared to ovariectomized rats. Ovariectomy caused a significant decrease in OPG gene expression in the tibia and aorta compared to sham operated rats. Although 17 beta-estradiol and raloxifene preserved gene expression in aorta they did not have any effect on bone tissue. OPG mRNA expression was negatively correlated with tissue MDA levels only in ovariectomized rats. Conclusion. This study confirms the increase in ovariectomy-induced oxidative stress and association of it to bone and vascular tissue OPG mRNA expression.
Keywords: Ovariectomy; Osteoprotegerin; Oxidative stress; HORMONE REPLACEMENT THERAPY; BONE-MINERAL DENSITY; KAPPA-B LIGAND; NITRIC-OXIDE; ESTROGEN DEFICIENCY; VASCULAR CALCIFICATION; RECEPTOR ACTIVATOR; ENDOTHELIAL DYSFUNCTION; POSTMENOPAUSAL WOMEN; OSTEOPOROSIS